Data Profiteering: Corporate Social Responsibility and Privacy Law Lost in Data Monetization and National Security - Taschner, John B. (American Journal of Trade and Policy, 2020)
Data mining and collecting is increasingly becoming a common practice, in the name of monetization of personal data, progression of national security measures, and politically fueled democratic interferences. Millions of users’ data is constantly being sorted, manipulated, and sold, often without conscientious consent of the consumer. While this practice can result in greater convenience from an innocent consumer level, the vulnerabilities to national privacy and the cyberspace create dangerous territory. The article entitled describes the triangulation of security, monetization, and politicizing in terms of data collection through three primary case studies: Cambridge Analytica and the Facebook scandal during the 2016 United States presidential election, Apple v. FBI, and Edward Snowden and the NSA surveillance activities. It explores how data harvesting and subsequent monetization is embedded in virtually every aspect of our culture and develops understanding of how corporate social responsibility calls for companies to respect and maintain transparency with consumer interests. Current technology policies leaves open spaces for violation both internally and internationally, and why this constitutes certain offensive measures. Future data and privacy legislation, with strong consideration to the varying social contexts, resources, and current international relations. This is done under the underlying assumption that data is an irreplaceable factor in our global progression and is irrevocably embedded into our society. Over-regulation or under-regulation of big tech may lead to negative repercussions to our security or individual privacy rights. These ideas are becoming increasingly understood by the general public and are considered worthy of concern after seeing glimpses of the depth of surveillance and information held by either the government or corporations. While there are intense emotions and opinions on the matter, my article takes an objective and well-rounded perspective to address the interlocking complexities of individual freedoms, need for international cyberspace protection, and continued profitability of data. The idea of personal data and information being manipulated and used against citizens for financial or political agendas is rightfully horrifying the public; my article therefore takes into account these concerns while suggesting further navigating the political, legal, and social process in alignment with the ever-growing power of big data.